Is exporting maize really bad? - Baulch, Bob (2017)
In recent days, MDF troops have been deployed to the northern border to prevent the smuggling of maize into Tanzania and Zambia. While this action seems a natural response during a year of national food shortage, four factors should give us pause for thought.